Corporate Tax Reforms With Policy Uncertainty - Pavel Brendler; Arpad Abraham; Eva Carceles (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
One important feature of tax reforms, in particular corporate tax reforms, is the uncertainty surrounding them. Are they going to be permanent or are they likely to be withdrawn by the subsequent government? The expected duration of the reform is important because it affects households' economic decisions, their expected welfare and ultimately their political support for the reform. We use a framework with heterogeneous agents who face uninsurable labor productivity shocks and a representative firm who pays capital adjustment costs. The model is calibrated to the U.S. in 2016. Our revenue-neutral reform eliminates corporate taxes on firm's profits at the cost of more progressive taxes on households' labor incomes. The duration of this reform is uncertain, since it can be repealed at given points in time in the future. Using this framework, we analyze the effect of uncertainty in reform duration on the political support for the reform.
Keywords: E20; E44; H24; H31; 330; Incomplete markets; Heterogeneous agents; Policy uncertainty; Tax reform